Tingkat pendidikan orang tua dan perbedaan pola asuh: Implikasi untuk pembentukan karakter anak - Ranu, Andarini (Maliki Interdisciplinary Journal, 2024)
Home becomes the first place to learn something new and in this case, parents are the first guide for a child. Parents have full responsibility for the needs of a child. This need is not only material but also non-material as physical and mental. This fulfillment can begin with a good pattern of caring in shaping the child's character. The pattern is adapted to the child and also the intellectual level of the parent. Parents' level of intelligence is sometimes determined by their level of education. In this article, we will discuss the correlation between the educational level of parents and the patterns used in forming the character of the child.